The broadcast century and beyond - Hilliard, Robert L., 1925- (Focal Press, 2010)
The Broadcast Century and Beyond is a popular history of the most influential and innovative industry of the century. The story of broadcasting is told in a direct and informal style, blending personal insight and authoritative scholarship to fully capture the many facets of this dynamic industry. The book vividly depicts the events, people, programs, and companies that made television and radio dominant forms of communication. The latest edition includes coverage of all the technologies that have emerged over the past decade and discusses the profound impact they have had on the broadcasting industry in political, social, and economic spheres. "Broadcasting" as a whole has been completely revolutionized with the advent of YouTube, podcasting, iphones, etc, and the authors show how this closing of world-wide broadcasting channels affects the industry. * A single-source of broadcast history-covers past and present influences on broadcast communications, and showcases trends both old and emerging in the broadcast industry * Chronological approach, timelines, and contextualizing sidebars help orient readers and demonstrate key implications of broadcasting history and broadcasting of today * Updated to reflect new and emerging technologies of the past decade, including podcasts, web, blogging, and more * Companion website provides further contextualizing information regarding the cultural climate surround events in broadcast history, and points to extensive resources -Instructions on how to access the website may be found in the book.-Please visit http://booksite.focalpress.com/hilliard.